Pengaruh Persepsi Risiko Dan Hambatan (Hbm) Terhadap Adopsi Skrining Kanker Serviks Pada Wanita Usia Produktif - Dianaulina, Dwi; Fajar, Nur Alam; Rahmiwati, Anita (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
Cervical cancer is one of the leading causes of death among women worldwide, particularly in developing countries. Early screening through Visual Inspection with Acetic Acid (VIA) and Pap smear has been proven effective in reducing incidence and mortality; however, screening coverage remains low. The Health Belief Model (HBM) is frequently applied to understand health-related behaviors, including cervical cancer screening. Literature indicates that perceived risk (perceived susceptibility and severity) and perceived barriers are critical constructs influencing the adoption of screening practices. This review aims to analyze studies published between 2020 and 2025 regarding the influence of perceived risk and barriers on cervical screening uptake using VIA and Pap smear. The findings reveal that low perceived risk reduces the intention to undergo screening, while perceived barriers (such as cost, embarrassment, lack of information, and limited access) consistently hinder participation. HBM-based interventions that emphasize risk awareness and barrier reduction have been shown to effectively increase screening uptake.